Strategic development of the innovative potential of industrial enterprises - S. G. Vagin (Управление)
The purpose of the article is to evaluate theoretical approaches to the study of various scientific and practical approaches of sustainable economic development. The author of the work has the following tasks: to conduct a comparative assessment of various scientists and economists studying theoretical approaches of sustainable strategic development of innovative potential of industrial enterprises; to identify the main directions of the theoretical approaches to its research of both Russian and foreign scientists; to determine the vectors of the strategic development of the innovative potential of companies in the industrial sector; to analyse and classify the methods that scientists use to study the essence and typology of the innovative potential of industrial enterprises within the economic system. Finally, the theoretical approaches to the study of the sustainable development of the innovative potential of enterprises of the regional industrial complex have been evaluated and used, the research results are formulated. The methods and techniques of application of various innovative technologies, ways, etc. are considered and evaluated. At the present stage of sustainable economic development this is of great importance. The results of the conducted research can be applied while formulating directions for the industrial and spatial development of the country’s economic sectors as well as for the strategic development of the innovative potential of industrial enterprises.